Gambaran Kejadian Struma di RSU Negara Tahun 2019-2020 - Bharata, Bagus Sastra (E-Jurnal Medika Udayana; Vol 12 No 4 (2023): E-Jurnal Medika UdayanaDO - 10.24843/MU.2023.V12.i04.P18, 2023)
ABSTRACT Introduction: A goiter, also called a goiter, is a swelling of the neck due to enlargement of the thyroid gland due to thyroid gland disorders, which can be in the form of dysfunction or changes in the arrangement of the gland and its morphology can be in the form of diffuse or nodus Based on the results of research conducted, it is estimated that around 200 million people worldwide suffer from goiter. The results of research on goiter in Indonesia, show the prevalence of the total goiter rate (TGR) from 9.8% in 1998 to 11.1% in 2003. is still a public health problem in Indonesia and data on the incidence of goiters in Indonesia is still minimal. This study aims to obtain a description of the goiter based on age, gender, type of therapy. Met ho d : This study used a retrospective descriptive study, the sample used was the State Hospital patient with goiter who met the criteria, the sample collection method used medical records which were then processed using the SPSS program, then presented in a table form. Result : Female patients were the most suffering from goiter (68.3%) in this study. The highest incidence of goiters in this study was the type of toxic goiter, namely 25 people (61%). Conclusion : The highest incidence of goiter in the type of toxic goiter, female sex, age 45-54 years, and most types of operative therapy.   Keyword: Struma, Struma Nodusa, Goiter